Incorporación del Prof. Policard, como Doctor Honoris Causa, en la Facultad de Ciencias Médicas de Lima - Villarán, Carlos (1935)
Speech poe the Dean of the Faculty of Medical Sciences, Dr. Carlos Villar by imposing Professor Policard Insignia Doctor Honoris Causa.